Politics, Policies and the Dynamics of Aggregate Productivity in Colombia - Marcela Eslava; Marcela Melendez (Inter-American Development Bank (IDB), 2009)
This paper describes private actors involvement in Colombias policymaking process. While more transparent and formal channels are used to discuss horizontal policies, they are also less effective. The adoption of targeted policies, however, follows a faster track and depends more on political power than on those policies potential as engines for productivity growth. Data targeted policies and political characteristics across sector-region units are used to further characterize the different groups weight in policymaking, and the effect of the implied unbalance on aggregate productivity. Electoral weight and being represented by business groups and associations are found to be important determinants of the policy benefits received by a sector in a region, especially when activities are located in regions affected by armed conflict. It is also found that the resulting imbalance of policies damages aggregate productivity.
Keywords: O43; O25; P16; 330; Productivity; political economy; interest groups; targeted policies